2017
DOI: 10.1002/ccr3.758
|View full text |Cite
|
Sign up to set email alerts
|

An abscopal effect in a case of concomitant treatment of locally and peritoneally recurrent gastric cancer using adoptive T‐cell immunotherapy and radiotherapy

Abstract: Key Clinical MessageThe mechanism of abscopal effect is becoming clear by the progress of cancer immunology. A 54‐year‐old male with recurrent gastric cancer presented an abscopal effect after radiotherapy with concurrent adoptive T‐cell immunotherapy (immunoradiotherapy). Immunoradiotherapy has potential to induce abscopal effect by strengthening systemic antitumor immunity even in recurrent cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
19
0
2
Order By: Relevance
“…The abscopal effect has been reported in patients treated with immune checkpoint inhibitors after radiotherapy. An abscopal effect in a patient with gastric cancer has been reported only by Sato et al [ 15 ]; it occurred following radiotherapy plus concurrent adoptive T-cell immunotherapy. Abscopal effects may be very rare in patients with gastric cancer; when such patients require postradiotherapy treatment, alternatives to nivolumab may need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The abscopal effect has been reported in patients treated with immune checkpoint inhibitors after radiotherapy. An abscopal effect in a patient with gastric cancer has been reported only by Sato et al [ 15 ]; it occurred following radiotherapy plus concurrent adoptive T-cell immunotherapy. Abscopal effects may be very rare in patients with gastric cancer; when such patients require postradiotherapy treatment, alternatives to nivolumab may need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of regression was reported in only two cases. Sharabi et al [20] reported the rate of regression as 95% and Sato et al as unmeasurable [21]. Most patients that were classified as PR were reported to have a minimal disease.…”
Section: Reviewmentioning
confidence: 99%
“…More recently, Rosenberg et al found similar objective response rates with that treatment regimen in 93 patients, noting complete response rates of 12% for those given chemotherapy alone, 20% for chemotherapy plus 2-Gy total body irradiation, and 40% for those given chemotherapy plus 12 Gy [30]. In a case study of a patient with poorly differentiated adenocarcinoma (stage IIIC) that recurred after surgery who was given T-cell and DC therapy before and concurrently with RT [31], Sato et al observed signs of tumor shrinkage and improved performance status after the concurrent treatment. These results emphasize the diversity in tested combinations of T-cell therapies and RT, and suggest that the effects of these regimens depend on the type, dose and timing of RT relative to T-cell administration.…”
Section: Clinical Data Perspective and Ongoing Trialsmentioning
confidence: 88%